Analysis of train/turnout vertical interaction using a fast numerical model and validation of that model. (September 2014) - Wan, Chang; Markine, Valeri L; Shevtsov, Ivan Y
A two-dimensional (2D) finite element model has been developed for simulation and analysis of train/turnout vertical dynamic interactions at a common crossing. The model has been validated through field measurements and simulation results obtained using a three-dimensional (3D) multi-body system (MBS) model. The dynamic behaviour of three turnouts on the Dutch railway network was simulated using the 2D model. The simulation results were compared with measured data collected from the instrumented crossings containing corresponding turnouts. It was observed that the values of the vertical acceleration of the crossing nose obtained from the simulations were in good agreement with the measured values. The 2D model was verified by adapting the more intricate 3D MBS model established in the VI-Rail software. The vertical geometry of the rail used in the 2D model was obtained using the wheel trajectory from the 3D model. It was observed that the dynamic wheel forces in the two models were close to one another. From these results it was concluded that the 2D model is able to simulate train/turnout interactions with a good accuracy and thus it can be used instead of complex time-consuming numerical simulations.